Interfacial integrity of low-shrinkage composite restorations related to the filling technique and consistency - Perlatti D'Alpino, Paulo Henrique; Silva, Marilia Santos; Miranda Gonzalez, Alejandra Hortencia; Rodrigues, Flavia Pires [UNESP] (Taylor & Francis Ltd, 2014)
Purpose: To evaluate the influence of filling techniques and consistency of low-shrinkage composites on the bond strength and internal gap formation in Class I bonded restorations. Two low-shrinkage restorative systems (N'Durance/Septodont and Filtek Silorane/3M ESPE) were used to restore Class I preparations. Bulk increment, two oblique increments or two horizontal increments were performed and Filtek Z350XT was used as a control. Each increment was photoactivated for 40 s and the restored teeth were then stored for 24 h at 37 degrees C before being longitudinally sectioned and the internal margins of the restorations dyed with 1% acid-red propylene glycol solution for 20 s. The specimens were water rinsed and digital images were recorded for the internal gap formation (%) analysis. Stick-shaped specimens were also tested in tension to evaluate the bond strength. Comparative consistency of unset composites was also performed. N'Durance exhibited the highest incidence of internal gaps amongst all the filling techniques. Filtek Silorane showed no significant difference of internal gap formation in comparison with Filtek Z350XT, regardless of the filling technique. Filtek Z350XT exhibited the highest bond strength and N'Durance the lowest when horizontally applied; bond strength of Filtek Silorane was not influenced by the filling technique. Both Filtek Z350XT and N'Durance presented lower consistency. Low-shrinkage composites seem to present equivalent or inferior bond strength and internal gap formation when compared to the methacrylate composite. The quality of the Class I preparation is dependent on the material and filling techniques.
Keywords: low-shrinkage composites; bond strength; consistency